In-situ catalytic upgrading of coal pyrolysis tar over activated carbon supported nickel in CO2 reforming of methane. (15th August 2019) - Wang, Mingyi; Jin, Lijun; Zhao, Haibin; Yang, Xiaoyu; Li, Yang; Hu, Haoquan; Bai, Zongqing
Graphical abstract: Highlights: Catalytic upgrading of tar over Ni/AC is the combination of CRM and tar cracking. Catalytic upgrading makes the light tar content and yield increase remarkably. The average molecular weight of upgrading tar has an obvious decrease. 3- and 4-ring arenes in upgrading tar decline, and 1- and 2-ring arenes increase. Abstract: An integrated process of in-situ catalytic cracking of coal pyrolysis tar and CO2 reforming of methane (CRM) over activated carbon supported nickel (Ni/AC) was conducted to upgrade tar. The results show that a tar with more than 95 wt% light tar content can be obtained, and the light tar yield is increased by 52.5% at 650 °C over Ni/AC. In comparison to the non-upgrading tar, the content of light oil, phenol oil, naphthalene oil and wash oil over Ni/AC increases by 224%, 283%, 132% and 36%, respectively, and the average molecular weight of tar decreases from 279 to 160 amu. During the upgrading process, 3-ring and 4-ring arenes decline, accompanied by the remarkable increase of 1-ring and 2-ring arenes. Isotope trace method were used to explore the mechanism of the upgrading process. When CH4 was replaced by CD4 or 13 CH4, D and 13 C can be detected in the upgraded tar. The results reveal that Ni/AC catalyze both CRM and tar cracking simultaneously, the free radicals from CRM stabilize cracking fragments of coal tar to generate more light components. By comparing the fresh and spent catalysts, it can be confirmed there is no adsorption of heavy tar over Ni/AC during the upgrading process.